Generativity and quality of life in rural educators: a scoping review of the evidence in comparison with work and altruistic contexts - Gómez Domínguez, Cristian Enrique; Laborín Álvarez, Jesús Francisco; Cáñez Cota, León Alejandro (Anales de Psicología / Annals of Psychology, 2025)
Background: Generativity—the concern for guiding future generations and contributing to societal well-being—serves as an indicator of quality of life in various social contexts. This is especially pertinent among rural educators who may face limited organizational resources but benefit from community support. Method: Following PRISMA-ScR guidelines, this scoping review utilized databases like Scopus and Science Direct to explore the impact of generativity on rural educators’ objective and subjective quality of life, comparing findings with other work and altruistic contexts. Nineteen studies published in English between 2013 and 2023 were included. Results: In both work and altruistic settings, generativity positively correlates with life satisfaction, job satisfaction, and psychological well-being. Specifically, in rural educational environments where teachers face unique challenges yet develop strong community bonds and high subjective well-being, generativity is linked to personal satisfaction, resilience, community engagement, and cultural practices. Conclusions: The review underscores the importance of generativity in enhancing quality of life across societal activities, particularly among rural educators who influence educational outcomes and bolster community resilience. These findings suggest that fostering generativity through targeted professional development and community engagement programs could improve educators’ well-being and effectiveness, especially in resource-limited rural settings.